2007
DOI: 10.1017/s0016774600023568
|View full text |Cite
|
Sign up to set email alerts
|

New groundwater-level rise data from the Rhine-Meuse delta – implications for the reconstruction of Holocene relative mean sea-level rise and differential land-level movements

Abstract: Reconstructions of Holocene relative sea-level and groundwater-level rise are crucial for understanding the palaeogeographical and geological evolution of coastal plains, while also serving studies of differential land-level change, palaeoecology, and archaeology. At present, the quest for higher accuracy in sea-level reconstruction and for better understanding of differences between local groundwater-level curves is still ongoing.Studies of Holocene relative (ground)water change and sealevel change in the Net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(91 citation statements)
references
References 14 publications
2
88
1
Order By: Relevance
“…Assuming that both modern and earlier mean sea level (MSL) did not differ more than 10 cm between the Belgian and German North Sea coast (Kiden et al 2008), comparison between differing LGW curves has revealed a series of influencing variables (e.g. Roeleveld 1974;Van De Plassche 1982;Van Dijk et al 1991;Kiden 1995;Makaske et al 2003;Van De Plassche et al 2005Berendsen et al 2007;Kiden et al 2008).…”
Section: Reconstructing Paleogroundwater Rise By Peat Datingmentioning
confidence: 99%
See 4 more Smart Citations
“…Assuming that both modern and earlier mean sea level (MSL) did not differ more than 10 cm between the Belgian and German North Sea coast (Kiden et al 2008), comparison between differing LGW curves has revealed a series of influencing variables (e.g. Roeleveld 1974;Van De Plassche 1982;Van Dijk et al 1991;Kiden 1995;Makaske et al 2003;Van De Plassche et al 2005Berendsen et al 2007;Kiden et al 2008).…”
Section: Reconstructing Paleogroundwater Rise By Peat Datingmentioning
confidence: 99%
“…Van Dijk et al (1991) also illustrates that as a consequence of the rising MSL and increasing sedimentation, the effect of the decreasing river gradient is visible in local basal peat curves along the Rhine-Meuse (see Cohen 2003: Figure 2.3). Finally, if the riverbed cuts through its natural levees to create a more favorable river gradient, this creates a short-term increase followed by a steady decrease in the speed of local MHW rise, superimposing the long-term RSL rise (Berendsen et al 2007). …”
Section: Reconstructing Paleogroundwater Rise By Peat Datingmentioning
confidence: 99%
See 3 more Smart Citations